Analysis of macular microvasculature with optical coherence tomography angiography for migraine: A systematic review and meta-analysis - Ke, Weishaer; Yu, Naiji; Liu, Xin; Gu, Yuxiang; Qin, Qiyu; Ye, Zifan; Li, Yuhang; Wang, Kaijun; Chen, Min (Frontiers in Neurology, 2022)
Objective This study aimed to evaluate the features of macular microvasculature with optical coherence tomography angiography (OCTA) among migraine patients. Methods We systematically searched PubMed, Web of Science, Embase, and Cochrane Library for studies that evaluated the macular microvasculature of migraine patients. The weighted mean differences (WMDs) of the foveal avascular zone (FAZ), foveal superficial capillary plexus (SCP) vessel density (VD), parafoveal SCP VD, foveal deep capillary plexus (DCP) VD, and parafoveal DCP VD with 95% confidence intervals (CIs) among migraine with aura (MA) group, migraine without aura (MO) group, and healthy controls (HC) group were analyzed using a random-effect model. P < 0.05 was considered significant in statistical analyses. Publication bias was assessed using funnel plots and statistical tests (Egger's test and Begg's test). Results Nine studies covering 675 individuals were enrolled in this meta-analysis ultimately. The FAZ of MA patients was not significantly different from HC (WMD = 0.04, 95% CI −0.00 to 0.09). However, the FAZ of MA was significantly larger than that of HC after correction of publication bias by trim and fill method (WMD = 1.03, 95% CI 0.99 to 1.08). The FAZ of MO patients was similar to that of HC (WMD = 0.03, 95% CI −0.00 to 0.07), while smaller than that of MA patients (WMD = 0.05, 95% CI 0.01 to 0.09). VD of the SCP, either in the foveal or parafoveal area, was not significantly different among the three groups. As for DCP, VD in MA patients was lower when compared with HC in the parafovea (WMD = −1.20, 95% CI −1.88 to −0.51). Conclusions We found that there was a larger FAZ in MA compared with HC after adjusting for publication bias. The FAZ in MO was not significantly different from that in HC, but significantly lower than that in MA. There was no significant difference in either foveal or parafoveal VD of SCP among MA, MO, and HC participants, while the parafoveal VD of the DCP in MA was lower than that of the HC.